2016
DOI: 10.1097/mao.0000000000001122
|View full text |Cite
|
Sign up to set email alerts
|

A Historical Recount

Abstract: Objectives In evaluating the historical context of the first description of Menière’s disease, its association with migraine headaches is compelling. We have outlined the events and observations of Prosper Menière, which led him to establish a link between migraine headaches and his eponymous disease. Study Design Prosper Menière’s original French writings were translated by our group and used to recount his observations and thoughts. Miles Atkinson’s English translations were used as a reference. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Several cross-sectional studies have also reported a high frequency of migraine headaches in MD (Moshtaghi et al 2016) and migraine symptoms during the attacks (Radtke et al 2002;Lopez-Escamez et al 2015). In addition, migraine is associated with inner ear pathologies, including tinnitus, vertigo, and sudden sensorineural hearing loss (Chu et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Several cross-sectional studies have also reported a high frequency of migraine headaches in MD (Moshtaghi et al 2016) and migraine symptoms during the attacks (Radtke et al 2002;Lopez-Escamez et al 2015). In addition, migraine is associated with inner ear pathologies, including tinnitus, vertigo, and sudden sensorineural hearing loss (Chu et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…2–5 Even Prosper Meniere mentioned in his original papers that his patients all suffered from migraine. 6 While in the past, Meniere’s disease was thought to be autoimmune 7 or purely peripheral in etiology 8, current evidence points to migraine as the underlying etiology, which manifests with peripheral symptoms via change in the blood flow within the cochlea and vestibule as well as fluid extravasation in the tissues of the inner ear caused by trigeminal nerve activation, the nerve intimately involved with the symptoms of migraine. 3…”
Section: Diagnosis: Migraine-related Meniere’s Syndromementioning
confidence: 99%
“…Cochlear migraine consists of migraine and non‐vestibular ear symptoms 11 . Even earlier, in 1966, Atkinson termed MD “migraine in the ear,” characterized by hearing loss secondary to vasospasms in the inner ear 17 . Therefore, MD is theorized to be a manifestation of cochleovestibular migraine as both conditions share a common pathophysiology.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%